Implications of the use of Strontium Ranelate (SRAN) in periodontics, dental implantology, oral surgery, orthodontics and endodontics and its possibility of application as storage media for avulsed teeth - Britto, Amanda Cristine dos Santos; Lacerda, Priscila Bruna Gonçalves; Batista, Victor Eduardo de Souza; Martins , Christine Men (ARCHIVES OF HEALTH INVESTIGATION, 2021)
Dental avulsion is still public health problem and tooth replantation has important unsuccess rates due to root resorption. Strontium ranelate (SRAN) presents antiresorptive property on the bone tissue and stimulates bone formation. So we aimed to comprehensively review the literature to 1- understand the mechanism of action of SRAN regarding to its propaedeutic in periodontics, dental implantology, oral surgery, orthodontics and endodontics, 2- present the current scientific knowledge about the SRAN efficiency on tooth avulsion; 3- observe fails and gaps in the literature and open up for unexplored ideas for SRAN uses and applications. An electronic search was performed crossing the key words ‘strontium ranelate’, ‘periodontics’, ‘dental implantology’, ‘oral surgery’, ‘orthodontics’ and ‘endodontics’, PubMed/Medline, Lilacs and BBO electronic databases were searched for research articles, reviews of literature, animal laboratory studies and laboratory studies, which had been published in English until July 2020. Twenty-five articles fulfilled the inclusion and exclusion criteria. The available literature demonstrates that SRAN provides a really better propaedeutic on the bone tissue and that the topical applications show a lower risk of side effects. That open up new perspectives and for the use of SRAN as a potential storage media for avulsed teeth.